(untitled) (Historia, 2021)
Karel Schoeman has assembled and edited an anthology of documents relating to the war of 1899 to 1902 held by the South African Library in Cape Town. He states that the selection was made at random from material in the Library, but that 'the writings of the famous or prominent have as far as possible been avoided'. Virtually all the people quoted were living in some part of South Africa during the war.